2020
DOI: 10.1007/s10143-020-01325-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of external ventricular drainage for the management of posterior cranial fossa tumours: a systematic review

Abstract: Posterior cranial fossa tumours frequently develop hydrocephalus as first presentation in up to 80% of paediatric patients and 21.4% of adults, although it resolves after tumour removal in 70-90% and 96%, respectively. New onset hydrocephalus is reported in about 2.1% of adult and 10-40% of paediatric patients after posterior fossa surgery. There is no consensus concerning prophylactic external ventricular drainage (EVD) placement that is frequently used before posterior fossa lesion removal, as well in those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Nevertheless, preoperative treatment remains mandatory in symptomatic patients. Treatment options include perioperative placement of an external ventricular drain, endoscopic third ventriculostomy or the insertion of a CSF shunt [ 2 , 4 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, preoperative treatment remains mandatory in symptomatic patients. Treatment options include perioperative placement of an external ventricular drain, endoscopic third ventriculostomy or the insertion of a CSF shunt [ 2 , 4 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Posterior fossa tumors are often associated with hydrocephalus at presentation, which commonly resolves after tumor removal. Nevertheless, cerebrospinal fluid (CSF) shunting may be mandatory prior to tumor resection in symptomatic cases [ 2 , 4 , 27 ]. Furthermore, hydrocephalus may be attributable to concomitant hydrocephalus not related to the posterior fossa tumor in the rare case, necessitating permanent CSF diversion.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Compared to series using ETV as the treatment of choice, we encountered similar rates. [3,6,8,22] Moreover, Srinivasan et al recently showed that the use of an ETV before tumor resection did not prevent the need for postresection CSF diversion. [3] Based on their ndings they changed the practice at their institution again.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In the latter group, options are subdivided into external ventricular drain (EVD), endoscopic third ventriculostomy (ETV), or ventriculoperitoneal shunt (VPS) placement. 2,[7][8][9] A plethora of studies have reported results in each subgroup including long-term durability of ETV vs VPS. 3 Series report either homogenous, singlepathology cohorts or pool data from diverse P-FT pathologies.…”
mentioning
confidence: 99%